Optimization of relativistic laser–ion acceleration. (22nd December 2014) - Schreiber, J.; Bell, F.; Najmudin, Z.
Abstract: Experiments have shown that the ion energy obtained by laser–ion acceleration can be optimized by choosing either the appropriate pulse duration or the appropriate target thickness. We demonstrate that this behavior can be described either by the target normal sheath acceleration model of Schreiber et al. or by the radiation pressure acceleration model of Bulanov and coworkers. The starting point of our considerations is that the essential property of a laser system for ion acceleration is its pulse energy and not its intensity. Maybe surprisingly we show that higher ion energies can be reached with reduced intensities.